Caracterización y potencial de viabilidad celular de la membrana de huevo estudio in vitro - Bonilla Torres, Norvy Johanna; Leguizamon Zarate, Jessica Alexandra; Polindara Idrobo, John Steban; Sánchez Triana, John Jaiber (Universidad Antonio Nariño, 2023)
The eggshell membrane due to its morphological and chemical characteristics It is currently a biological material of great interest to the scientific community